2012
DOI: 10.1103/physreva.85.052709
|View full text |Cite
|
Sign up to set email alerts
|

Renner-Teller effect on dissociative electron attachment to carbon dioxide

Abstract: Stereo-dynamics of dissociative electron attachments to CO 2 is investigated by the O − anion velocity imaging experiments combined with the R-matrix calculations. 2 Π g as a Feshbach resonant state of CO 2 − is confirmed to play roles in the dissociations around 8.0 eV. We find that the dynamic evolutions of the Renner-Teller effect lead to the dramatically different anisotropic O − momentum distributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…12,13,17 The sliced images of I − are depicted in Figs 10 and the polarized molecular local bond 16 would indeed introduce a forward-backward asymmetry of the angular distribution, but they cannot be responsible for the present imagepattern evolution with the electron energy. Since the angular distributions are primarily relevant to the symmetries of the resonant states in the Franck-Condon region, 8,10,[12][13][14][15][16] all of these images should presumably show the typical up-anddown ( 2 state) or backward-forward ( 2 state) distributions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…12,13,17 The sliced images of I − are depicted in Figs 10 and the polarized molecular local bond 16 would indeed introduce a forward-backward asymmetry of the angular distribution, but they cannot be responsible for the present imagepattern evolution with the electron energy. Since the angular distributions are primarily relevant to the symmetries of the resonant states in the Franck-Condon region, 8,10,[12][13][14][15][16] all of these images should presumably show the typical up-anddown ( 2 state) or backward-forward ( 2 state) distributions.…”
mentioning
confidence: 99%
“…The state-of-the-art VMI technique enables us to identify different anionic fragments of the DEA process and record the angular distribution of a specific fragment in the full range θ = 0 = 2π . [12][13][14][15][16] In the Franck-Condon region of the vertical electron attachment, various resonant states of ICl − are accessible. The potential energy curves of both the neutral ICl at the ground state and the anion ICl − at the low-lying resonances were recalculated with the internally contracted multi-reference CI method including the SO coupling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Honestly, this type of two dimensional velocity slicing technique using time gate would take into account a larger fraction of the total solid angle for ions with lower momentum and a smaller fraction of solid angle for ions with larger momentum. In order to preserve the fraction of governed solid angle for any momentum to achieve better statistics, Moradmand et al [27] defines a conical gate through wedge slicing technique instead of flat time gate; resulting the data restricts by angle in a spherical momentum-space, rather than in one Cartesian coordinate [28,29]. As a counter response for this overestimation in 2D time gated flat slicing technique, in a very recent article [30] Nag et al reported a new technique to study the characteristic of very low-energy ions.…”
Section: Resultsmentioning
confidence: 99%
“…DEA to carbon dioxide can proceed via two low energy resonances: one at 4 eV is a shape resonance of 2 Π u symmetry that has been studied extensively by electron scattering [84,85,86,34,35,38,39,40,41,42,43] and DEA [36,87,88,89,90,37,91,92,93,94,33,78,53,54]. A second resonance occurs in DEA at electron impact energies near 8 eV [36,87,90,91,92,93,94,33,53,54,95,56,96]. This Feshbach resonance is understood to have a long autodetachment lifetime, such that the anion preferentially dissociates and the resonance is less prevalent in electron scattering cross sections [97,86,98].…”
Section: Conical Intersectionsmentioning
confidence: 99%